?PHARMACOLOGICAL EVALUATION OF THE ANTIEMETIC ACTION OF NELUMBIUM SPECIOSUM -WILD SEEDS - Yaqeen, Zahra; Mirza, Maryam; Khan, Yaqeenuddin; Ahmad, Kaneez Fatima; Badar, Yasmeen (Biological Sciences - PJSIR, 1998)
The antiemetic property of Nelumbium speciosum-wild was investigated in this study. The crude alcoholic and aqueous extracts of the decorticated seeds were found effective in controlling centrally induced emesis by apomorphine in dogs. A dose of 90 mg kg" body weight of the alcoholic extract given orally causes antiemetic effect in 3 h. However, the administration of a dose of 9000 mg kg:’ body weight of aqueous extract reduces the frequency of vomiting to only once in 3 h. The efficacy of Nelumbium speciosum wild extract, though in high doses, was found comparable with chlorpromazine (Largactil) and metoclopramide (Maxolon).